A novel anatomical short glass fiber reinforced post in an endodontically treated premolar mechanical resistance evaluation using acoustic emission under fatigue testing. (January 2017) - Wang, Hsuan-Wen; Chang, Yen-Hsiang; Lin, Chun-Li
Abstract: This study evaluates the fracture resistance in an endodontically treated tooth using circular fiber-reinforced composite (FRC) and innovated anatomical short glass fiber reinforced (SGFR) posts under fatigue testing, monitored using the acoustic emission (AE) technique. An anatomical SGFR fiber post with an oval shape and slot/notch design was manufactured using an injection-molding machine. Crown/core maxillary second premolar restorations were executed using the anatomical SGFR and commercial cylindrical fiber posts under fatigue test to understand the mechanical resistances. The load versus AE signals in the fracture and fatigue tests were recorded to evaluate the restored tooth failure resistance. The static fracture resistance results showed that teeth restored using the anatomical SGFR post presented higher resistance than teeth restored using the commercial FRC post. The fatigue test endurance limitation (1.2×10 6 cycles) was 207.1 N for the anatomical SGFR fiber post, higher than the 185.3 N found with the commercial FRC post. The average accumulated number of AE signals and corresponding micro cracks for the anatomical SGFR fiber post (153.0 hits and 2.44 cracks) were significantly lower than those for the commercial FRC post (194.7 hits and 4.78 cracks) under 40% of the static maximum resistance fatigue test load (pass 1.2×10 6 cycles). This study concluded that the anatomical SGFR fiber post with surface slot/notch design made using precise injection molding presented superior static fracture resistance and fatigue endurance limitation than those for the commercial FRC post in an endodontically treated premolar.